2006
DOI: 10.1016/j.ejcts.2006.03.028
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mitral valve surgery combined with maze procedure☆

Abstract: Patients with successful maze procedures resulted in higher survival rate, greater freedom from stroke and cardiac events. The large left atrium, small f-wave, and long AF duration were significant risk factors for failed maze procedures, suggesting that earlier surgical interventions would result in superior results in mitral valve surgery combined with maze procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 27 publications
1
46
0
3
Order By: Relevance
“…Earlier studies have detected various such factors, including old age, larger left atrial diameter, a long preoperative history of arrhythmia, lower amplitude of F wave, rheumatic mitral valve disease, permanent AF, and maze-lesion sets. [18][19][20][21][22] In our study, only arrhythmia duration longer than 36 months was confirmed as an adverse variable; other issues emerged unexpectedly, and their significant role was corroborated by multiple statistical tools that we also used to evaluate the intrinsic nature of the arrhythmia (that is, its chance of recurring several times). 17 First, we conf irmed the importance of discharge rhythm, as was pointed out by Lazopoulos and colleagues 15 ; the consequent clinical application consists in prompt cardioversion of every tachyarrhythmia.…”
Section: Months After Maze Proceduresmentioning
confidence: 81%
“…Earlier studies have detected various such factors, including old age, larger left atrial diameter, a long preoperative history of arrhythmia, lower amplitude of F wave, rheumatic mitral valve disease, permanent AF, and maze-lesion sets. [18][19][20][21][22] In our study, only arrhythmia duration longer than 36 months was confirmed as an adverse variable; other issues emerged unexpectedly, and their significant role was corroborated by multiple statistical tools that we also used to evaluate the intrinsic nature of the arrhythmia (that is, its chance of recurring several times). 17 First, we conf irmed the importance of discharge rhythm, as was pointed out by Lazopoulos and colleagues 15 ; the consequent clinical application consists in prompt cardioversion of every tachyarrhythmia.…”
Section: Months After Maze Proceduresmentioning
confidence: 81%
“…Although the surgical results of the maze procedure for cases of atrial fibrillation concomitant with mitral diseases have been shown to be excellent, 19,20) the results for maze treatment of atrial fibrillation associated with rheumatic mitral disease have been reported to be somewhat less effective. [21][22][23] Such an outcome appears to be quite consistent with the results of our study group, for which the conversion rate to normal sinus rhythm was 38.9% at the latest follow-up, a figure which was far lower than the results reported by others.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies described some risk factors for late failure of sinus rhythm restoration such as the presence of an enlarged left atrium, fine fibrillation wave size, and longer duration of Af in cases of atrial fibrillation concomitant with mitral surgery. 20,22,24) On the basis of such results, in 1998, Fukada and associates 21) even went to the extent of suggesting that the indications for the maze procedure for Af associated with rheumatic mitral disease might need to be reconsidered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dieser Anteil sank nach 15 Jahre langsam auf 40%. Ob eine postoperative Konversion in einen normalen Sinusrhythmus die Überlebenschancen tatsächlich verbessert, scheint auf Grund von Literaturangaben unwahrscheinlich; vorläu-fig ebenfalls nicht schlüssig zu beantworten ist, ob eine Vorhofsprozedur den normalen Sinusrhythmus postoperativ auch längerfristig stabilisiert und sich lebensverlängernd auswirkt [22][23][24][25][26].…”
Section: Abbildungunclassified